Grating Pair Wavepacket Shaper for Crafting Spatiotemporal Optical Vortices with Arbitrary Tilt Angles - Jordan Adams; Andy Chong (Photonics)
Spatiotemporal optical vortices with arbitrary tilt angles can be generated by adjusting spatial chirp and beam size at a phase modulation plane in a pulse shaper setup. A grating pair setup is proposed to generate variable spatial chirp independent of the beam profile. The initial dispersion of the pulse allows for the independent control of the vortex orientation. By adjusting the beam size, spatial chirp, and initial dispersion, arbitrary vortex orientation across all the possible angles can be achieved. The ability to achieve arbitrary vortex orientations at long propagation distances could offer significant advantages for long-distance communication applications.